Device engineering for all-inorganic perovskite light-emitting diodes - Luo, Dongxiang (2020)
Recently, all-inorganic perovskite light-emitting diodes (PeLEDs) have attracted both academic and industrial interest thanks to their outstanding properties, such as high efficiency, bright luminance, excellent color purity, low cost and potentially good operational stability. Apart from the design and treatment of all-inorganic emitters, the device engineering is another significant factor to guarantee the high performance. In this review, we have summarized the state-of-the-art concepts for device engineering in all-inorganic PeLEDs, where the charge injection, transport, balance and leakage play a critical role in the performance. First, we have described the fundamental concepts of all-inorganic PeLEDs. Then, we have introduced the enhancement of device engineering in all-inorganic PeLEDs. Particularly, we have comprehensively highlighted the emergence of all-inorganic PeLEDs, strategies to improve the hole injection, approaches to enhance the electron injection, schemes to increase the charge balance and methods to decrease the charge leakage. Finally, we have clarified the issues and ways to further enhance the performance of all-inorganic PeLEDs.